ТЕОРЕТИКО-МЕТОДОЛОГІЧНІ ЗАСАДИ ДОСЛІДЖЕННЯ ЕКОЛОГІЧНОЇ СК ЛАДОВОЇ В СТРУКТУРІ УКРАЇНСЬКОЇ ПОЛІТИКИ (СУЧАСНИЙ ФІЛОСОФСЬКИЙ ДИСК УРС) - Концурак, О. (Hileya: Scientific Bulletin / Gileya, 2017)
Environmental issues are increasingly moving to the forefront of sociohumanitarian and science–based programs and research. And this is understandable. According to experts, the acuity of environmental safety has reached such a level, inactivity ignoring which can lead not only to destruction or collapse, but also to the final destruction of human life. The prospect of an ecological collapse of the Planet becomes quite real. It is also threatening in Ukraine. Negative consequences of the Chernobyl accident, catastrophic pollution of air, water and soil, excessive concentration of industry in certain regions, inefficient use of natural resources, demographic crisis – even this, far from being a complete list of negative factors, poses a real threat to the national security of Ukraine in the environmental sphere. The need for urgent correction of the situation becomes more pain than obvious.